2016
DOI: 10.1002/14651858.cd007077.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Partial breast irradiation for early breast cancer

Abstract: It appeared that local recurrence and 'elsewhere primaries' (new primaries in the ipsilateral breast) are increased with PBI/APBI (the difference was small), but we found no evidence of detriment to other oncological outcomes. It appeared that cosmetic outcomes and some late effects were worse with PBI/APBI but its use was associated with less acute skin toxicity. The limitations of the data currently available mean that we cannot make definitive conclusions about the efficacy and safety or ways to deliver of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 95 publications
1
36
0
2
Order By: Relevance
“…Some studies have reported that breast cancer patients who received APBI report satisfaction with treatment [58] and good cosmetic outcomes [5,22,59], while other studies reported unacceptable cosmetic outcomes following APBI [60,61]. In a systematic review of published and unpublished trials, PBI/APBI was associated with lower likelihood of acute, but not late, skin toxicity compared with WBRT, although cosmetic outcome and local recurrence-free survival appeared to be worse with PBI/APBI in the studies reviewed [15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that breast cancer patients who received APBI report satisfaction with treatment [58] and good cosmetic outcomes [5,22,59], while other studies reported unacceptable cosmetic outcomes following APBI [60,61]. In a systematic review of published and unpublished trials, PBI/APBI was associated with lower likelihood of acute, but not late, skin toxicity compared with WBRT, although cosmetic outcome and local recurrence-free survival appeared to be worse with PBI/APBI in the studies reviewed [15]. …”
Section: Discussionmentioning
confidence: 99%
“…However, a number of systematic reviews reported a lack of evidence about short-term RT side effects and their impact on changes in quality of life (QOL) [1114]. One review of randomized clinical trials comparing PBI/APBI and conventional or hypo-fractionated WBRT found that no studies reported on the relative effects of PBI/APBI and WBRT on quality of life [15]. …”
Section: Introductionmentioning
confidence: 99%
“…The results of these clinical trials demonstrated diverging outcomes related to local recurrence rates, while establishing comparable similar survival outcomes for APBI and WBI . A systematic review and a meta‐analysis assessed the effectiveness and outcomes of APBI compared to WBI in early‐stage breast cancer, confirming that APBI was associated with a small but statistically significant increase in local recurrence rates …”
Section: Discussionmentioning
confidence: 77%
“…The authors found that local recurrences and new primary ipsilateral tumors were more common with APBI, without differences in survival. Due to the limitations of the included data, the authors did not make any definite conclusions about the safety and efficacy of APBI …”
Section: Clinical Evidence For Apbimentioning
confidence: 99%
See 1 more Smart Citation